ANALISIS EFEKTIVITAS PROGRAM KESEHATAN IBU YANG DIDANAI BANTUAN OPERASIONAL KESEHATAN DI PUSKESMAS BANDARHARJO KOTA SEMARANG - Ananda Suryo Adi Prayogo; Antono Suryoputro; Ayun Sriatmi (Jurnal Kesehatan Masyarakat (Undip), 2017)
Health Operational Aid is a government program of the Ministry of Health devoted to helping health centers in an effort to society in terms of health promotion and prevention. One of the utilization BOK funds activitiesis maternal health programs.Based on secondary data, Bandarharjo’s Public Health Center allocate BOK funds highest for maternal health programin the city of Semarang amounted Rp. 28,360,000.00,-. A program is said to be effective if the desired goals or objectives can be achieved in accordance with the plan and can give the desired results. Maternal health programs can be considered effective if it can prevent death in pregnant women. But, Bandarharjo’s Public Health Center has the highest number of maternal death case in the city of Semarang with 5 death cases.This research aims to determine the effectiveness of maternal health programs funded by the Health Operational Aid in Bandarharjo Health Center in the city of Semarang seen from several variables that are resources, budget, guidelines, facilities, planning, mobilizing implementation, monitoring assessment and the gains of maternal health programs. This research is a qualitative with in-depth interviews were conducted in Head of the Public Health Centers, Public Health Centers BOK Treasurer, Program Coordinator of Maternal Public Health Centers, Health Workers, Pregnant Women, BOK Treasurer and Head of KIA Semarang City Health Department.Research results shows that the implementation of maternal health programs funded Health Operational Aid in Bandarharjo Public Health Center is still not effective.This is because the number of officers are still lacking, BOK limited budget, lack of valid supporting data plan, the system is not clear division of tasks,some pregnant women who do not want be accompanied and the level of public awareness is still low.